UTILIZING MAGNETIC MATERIALS IN TECHNICAL APPLICATIONS - Maxmudova Dilafruz Xasanovna; Sagidullayeva Munira Muhidovna (Web of Journals Publishing, 2024)
This article discusses the use of magnetic materials in engineering and their main characteristics.
Keywords: metallurgy, alloy, magnetic, materials, ferromagnetic, electron spins, electrolytes.